Overexpression of OsC3H10, a CCCH-Zinc Finger, Improves Drought Tolerance in Rice by Regulating Stress-Related Genes - So Yoon Seong; Jae Sung Shim; Seung Woon Bang; Ju-Kon Kim (Plants, 2020)
CCCH zinc finger proteins are members of the zinc finger protein family, and are known to participate in the regulation of development and stress responses via the posttranscriptional regulation of messenger RNA in animals and yeast. However, the molecular mechanism of CCCHZF-mediated drought tolerance is not well understood. We analyzed the functions of OsC3H10, a member of the rice CCCHZF family. OsC3H10 is predominantly expressed in seeds, and its expression levels rapidly declined during seed imbibition. The expression of OsC3H10 was induced by drought, high salinity and abscisic acid (ABA). Subcellular localization analysis revealed that OsC3H10 localized not only in the nucleus but also to the processing bodies and stress granules upon stress treatment. Root-specific overexpression of OsC3H10 was insufficient to induce drought tolerance, while the overexpression of OsC3H10 throughout the entire plant enhanced the drought tolerance of rice plants. Transcriptome analysis revealed that OsC3H10 overexpression elevated the expression levels of genes involved in stress responses, including LATE EMBRYOGENESIS ABUNDANT PROTEINs (LEAs), PATHOGENESIS RELATED GENEs (PRs) and GERMIN-LIKE PROTEINs (GLPs). Our results demonstrated that OsC3H10 is involved in the regulation of the drought tolerance pathway by modulating the expression of stress-related genes.